2017
DOI: 10.1002/admt.201700136
|View full text |Cite
|
Sign up to set email alerts
|

Batch Fabrication of Customizable Silicone‐Textile Composite Capacitive Strain Sensors for Human Motion Tracking

Abstract: This paper presents design and batch manufacturing of a highly stretchable textile-silicone capacitive sensor to be used in human articulation detection, soft robotics and exoskeletons. The proposed sensor is made of conductive knit fabric as electrode and silicone elastomer as dielectric. The batch manufacturing technology enables production of large sensor mat and arbitrary shaping of sensors, which is precisely achieved via laser cutting of the sensor mat. Individual capacitive sensors exhibit high linearit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
277
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(289 citation statements)
references
References 64 publications
1
277
0
3
Order By: Relevance
“…However, it should be noted that this linear relationship is not valid for the utilized polymer if the strain is too large. [46] To fabricate textile-based capacitive sensors, [51][52][53] multiple electrodes are placed on one side the textile materials surface, opposed to other ones on the other side of the textile structure, which is flexible material. [15] For instance, Baughman et al [54,55] fabricated a dielectric fiber-shaped capacitor-based strain sensor with good sensitivity as well as high linearity within a large strain range.…”
Section: Capacitive Sensormentioning
confidence: 99%
“…However, it should be noted that this linear relationship is not valid for the utilized polymer if the strain is too large. [46] To fabricate textile-based capacitive sensors, [51][52][53] multiple electrodes are placed on one side the textile materials surface, opposed to other ones on the other side of the textile structure, which is flexible material. [15] For instance, Baughman et al [54,55] fabricated a dielectric fiber-shaped capacitor-based strain sensor with good sensitivity as well as high linearity within a large strain range.…”
Section: Capacitive Sensormentioning
confidence: 99%
“…These textiles have the characteristics of softness, light weight, and breathability and, thus, the potential for realizing comfort in wearable electronics. In recent years, intensive endeavors have been devoted to develop textile-based systems in sensitive sensors, energy harvesting, and storage (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). In particular, successful research has been reported on optical fiber, piezoelectricity, and resistivity-based smart textiles applied in the monitoring of pulse and respiratory signals (40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…While originally derived for static plate capacitors, this relationship also holds for capacitors made from silicone elastomers [Atalay et al 2017;Huang et al 2017;O'Brien et al 2014]. To minimize capacitive coupling effects with other objects, capacitors are typically shielded via insulating layers (see inset).…”
Section: Electrode Electrodementioning
confidence: 99%